2010
DOI: 10.1038/onc.2010.252
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional factor HBP1 targets P16INK4A, upregulating its expression and consequently is involved in Ras-induced premature senescence

Abstract: Oncogene-mediated premature senescence has emerged as a potential tumor-suppressive mechanism in early cancer transitions. Many studies showed that Ras and p38 mitogen-activated protein kinase (MAPK) participate in premature senescence. Our previous work indicated that the HMG box-containing protein 1 (HBP1) transcription factor is involved in Ras-and p38 MAPK-induced premature senescence, but the mechanism of which has not yet been identified. Here, we showed that the p16 INK4A cyclin-dependent kinase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 46 publications
6
57
0
Order By: Relevance
“…Confoundingly, we and others have reported that HBP1 can transcriptionally activate genes such as those for p16, p21 (29), MPO (30,31), and histone H1 (32), but the mechanism was unclear. Our previous work shows that protein acetylation is critical for p16 regulation (33,34), consistent with many reports of acetylation on other factors (e.g., MTA1, p63, CtBP, and NuRD [35][36][37]). Given its regulation of important cell cycle regulators, it is not surprising that overexpression of HBP1 induces cell cycle arrest and premature senescence in numerous cells and in organs (16,21,38,39).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…Confoundingly, we and others have reported that HBP1 can transcriptionally activate genes such as those for p16, p21 (29), MPO (30,31), and histone H1 (32), but the mechanism was unclear. Our previous work shows that protein acetylation is critical for p16 regulation (33,34), consistent with many reports of acetylation on other factors (e.g., MTA1, p63, CtBP, and NuRD [35][36][37]). Given its regulation of important cell cycle regulators, it is not surprising that overexpression of HBP1 induces cell cycle arrest and premature senescence in numerous cells and in organs (16,21,38,39).…”
supporting
confidence: 70%
“…We previously reported that HBP1 induces premature senescence through transcriptional activation of the p16 gene (33,34). We next asked if varying DNMT1 levels and DNA methylation might influence the interaction of HBP1 with the p16 promoter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] This supports the idea that different pathways of carcinogenesis affect treatment response and outcomes. The high 26,27 A large body of published data in the context of oropharyngeal and supraglottic squamous cell carcinoma confirm that p16 INK4a overexpression predicts increased radiosensitivity and improved survival. [11][12][13][14][15][16][17][18] Published data specific to oral cavity squamous cell carcinoma examining p16 INK4a , HPV status, and outcome are more limited.…”
Section: Discussionmentioning
confidence: 99%